High‐Lithiophilicity Host with Micro/Nanostructured Active Sites based on Wenzel Wetting Model for Dendrite‐Free Lithium Metal Anodes. (16th September 2021) - Mei, Yang; Zhou, Jiahui; Hao, Yutong; Hu, Xin; Lin, Jiao; Huang, Yongxin; Li, Li; Feng, Changgen; Wu, Feng; Chen, Renjie
Abstract: Superior lithophilicity for the 3D host is essential to enable both uniform molten lithium (Li) infusion during synthesis and a low Li nucleation barrier during cycling. The wetting behavior between the host surface and molten Li can be reasonably predicted by the typical Wenzel model. Herein, inspired by the model, a lotus‐leaf‐like carbon nanotube (CNT)/NiO spheres hybrid structure is employed to improve the wettability and regulate Li plating/stripping. First, the CNTs interweave to form a highly conductive and robust sponge with accelerated Li + transport and reinforced stability. Second, the embedded NiO microspheres possess the Li‐active nature. More importantly, the surface roughness caused by nano‐sized protuberances over its surface further stronger the lithiophilicity. By the in situ optical microscope and calculations, this multistage structure is proven to homogenize the Li deposition and inhibit dendrite growth. As a result, the composite anode enables excellent cycling performance at both symmetric and full cells. This design of micro/nanostructured host provides a new perspective on the development of an excellent wettable host for Li‐metal anode. Abstract : A hierarchical carbon nanotube (CNT) @ NiO framework is constructed to improve the lithiophilicity and stabilize the lithium metal anode combining chemical optimization and architecture building. The high conductive CNT sponge and the lithiophilic micro‐nanostructured NiO spheres with nano‐sized protuberances over the surface synergistically promote the uniform Li + deposition. Finally, the electrochemical performance of lithium metal battery using the CNT@NiO host is effectively improved.